Microplastics alter composition of fungal communities in aquatic ecosystems - Kettner, Marie Therese (2017)
Despite increasing concerns about microplastic (MP) pollution in aquatic ecosystems, there is insufficient knowledge on how MP affect fungal communities. In this study, we explored the diversity and community composition of fungi attached to polyethylene (PE) and polystyrene (PS) particles incubated in different aquatic systems in north‐east Germany: the Baltic Sea, the River Warnow and a wastewater treatment plant. Based on next generation 18S rRNA gene sequencing, 347 different operational taxonomic units assigned to 81 fungal taxa were identified on PE and PS. The MP‐associated communities were distinct from fungal communities in the surrounding water and on the natural substrate wood. They also differed significantly among sampling locations, pointing towards a substrate and location specific fungal colonization. Members of Chytridiomycota, Cryptomycota and Ascomycota dominated the fungal assemblages, suggesting that both parasitic and saprophytic fungi thrive in MP biofilms. Thus, considering the worldwide increasing accumulation of plastic particles as well as the substantial vector potential of MP, especially these fungal taxa might benefit from MP pollution in the aquatic environment with yet unknown impacts on their worldwide distribution, as well as biodiversity and food web dynamics at large.